2021
DOI: 10.3389/fonc.2021.735183
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of EGFR/PKC-δ/NF-κB Signaling Associated With Imipramine-Inhibited Progression of Non-Small Cell Lung Cancer

Abstract: BackgroundAnti-depressants have been reported to own anti-tumor potential types of cancers; however, the role of imipramine in non-small cell lung cancer (NSCLC) has not been elucidated. Epidermal growth factor receptor (EGFR) was known to be one of the key regulators that control NSCLC progression. Whether EGFR would be the target of imipramine for suppressing tumor signaling transduction and results in anti-tumor potential is remaining unclear.MethodsWe used CL-1-5-F4 cells and animal models to identify the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…For example, PKCι/λ and PKCζ, are now considered fundamental regulators of tumorigenesis [31]; PKCε acts as a key regulator of mitochondrial redox homeostasis in acute myeloid leukemia [32]. Among different isoforms, PKCδ was reported as a critical regulator of immune homeostasis and closely involved in autoimmune disease and cancer progression [21,33]. The oncogenic role of PKCδ has been demonstrated in preclinical and clinical data, including promotion of lung KRAS-dependent tumorigenesis [34] and negative correlation with the prognosis of ErbB2-driven tumorigenesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…For example, PKCι/λ and PKCζ, are now considered fundamental regulators of tumorigenesis [31]; PKCε acts as a key regulator of mitochondrial redox homeostasis in acute myeloid leukemia [32]. Among different isoforms, PKCδ was reported as a critical regulator of immune homeostasis and closely involved in autoimmune disease and cancer progression [21,33]. The oncogenic role of PKCδ has been demonstrated in preclinical and clinical data, including promotion of lung KRAS-dependent tumorigenesis [34] and negative correlation with the prognosis of ErbB2-driven tumorigenesis [35].…”
Section: Discussionmentioning
confidence: 99%
“…The next day, cells were spun down (2,000 rpm, 10 min), washed with PBS, and stained with propidium iodide in the dark (37˚C for 20 min), and then analyzed by the NovoCyte flow cytometer with the NovoExpress ® software (Agilent Technologies Inc., Santa Clara, CA, USA) (21). For apoptosis measurements, cells were stained by cleaved-caspase 3, 8, 9, Fas, Fas-L, DIOC 6 , and Annexin V-PI reagent in the dark for 30 min at 37˚C (22,23).…”
Section: Methodsmentioning
confidence: 99%
“…The 2-well insert was then removed. Finally, cell the migration pattern was automatically observed by the IncuCyte S3 System (Sartorius, Göttingen, Germany), and images were taken using a IncuCyte S3 system at 0 h, 12 h and 24 h (22).…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, for non-small-cell lung cancer (NSCLC), the in vivo and in vitro studies performed by Yueh et al reported that imipramine was able to induce intrinsic and extrinsic apoptosis and reduced the invasion and the migration potential of NSCLC cells. In this case, the triggers of this antitumor effect seemed to be the increase in DNA damage and the decrease in phosphorylation of EGFR/PKC-δ/NF-κB and their downstream proteins [73]. In this line, the study performed by Zinnah et al showed that amitriptyline could sensitize TRAIL-resistant A549 lung cancer cells to tumornecrosis-factor-related apoptosis-inducing ligand (TRAIL) and enhance TRAIL-induced apoptosis through DR4 and DR5 upregulation and autophagy inhibition [74].…”
Section: Lung Cancermentioning
confidence: 97%